CHRONIC INTOXICATION WITH TOBACCO AS A FACTOR REDUCING CONCENTRATION OF ANTIBIOTICS WHEN TREATING PULMONARY TUBERCULOSIS AND COMMUNITY-ACQUIRED PNEUMONIA - A. S. Shprykov; D. A. Sutyagina (Туберкулез и болезни лёгких)
.